2018
DOI: 10.3390/ani8100172
|View full text |Cite
|
Sign up to set email alerts
|

N Balance Studies Emphasize the Superior Protein Quality of Pig Diets at High Inclusion Level of Algae Meal (Spirulina platensis) or Insect Meal (Hermetia illucens) when Adequate Amino Acid Supplementation Is Ensured

Abstract: Simple SummaryThis study aimed to evaluate diets with complete substitution of soybean meal (SBM) by an algae meal from Spirulina platensis (SM) or partly defatted larvae meal from Hermetia illucens (HM) as feed for piglets and growing pigs. Main feed ingredients of the experimental diets were wheat, barley, and SM or HM. The final diets contained 21% (piglets) and 13% (growing pigs) of SM or HM and nitrogen (N) balance studies were applied to measure parameters of apparent N digestibility, complex dietary pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…Remarkable feeding efficiencies and the ability to upcycle nutrient-poor substrates into protein-rich insect biomass are prime characteristics of commercial interest [ 19 21 ]. Given their valuable nutrient profiles [ 22 , 23 ], BSF larvae are highly suited for partially replacing soybean and fishmeal in diets for poultry [ 24 , 25 ], swine [ 26 , 27 ] and aquaculture species [ 28 , 29 ]. Moreover, their high-fat contents could serve as a source for biodiesel [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable feeding efficiencies and the ability to upcycle nutrient-poor substrates into protein-rich insect biomass are prime characteristics of commercial interest [ 19 21 ]. Given their valuable nutrient profiles [ 22 , 23 ], BSF larvae are highly suited for partially replacing soybean and fishmeal in diets for poultry [ 24 , 25 ], swine [ 26 , 27 ] and aquaculture species [ 28 , 29 ]. Moreover, their high-fat contents could serve as a source for biodiesel [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In their feeding trials with piglets and barrows, Neumann et al [ 19 ] observed that soybean meal could be completely replaced by spirulina (with appropriate lysine supplementation) in swine diets without compromising overall protein quality. However, the authors also observed that supplementing histidine in high amounts when in combination with lysine, methionine and threonine improves protein quality of swine diets containing spirulina [ 19 ]. In additional trials, spirulina as a feed did result in slightly lower carcass weights, however, results remained insignificant compared to the soybean meal-fed group [ 20 ].…”
Section: Spirulina In Swine Feedmentioning
confidence: 99%
“…Some common insects used in the production of IM include the black soldier fly, yellow mealworm, and the common housefly [ 136 ]. The complete or partial substitution of SBM with defatted IM (from black soldier fly larvae) in diets of piglets and growing pigs revealed no differences in growth performance, pork quality, sensory parameters, and an increase in nitrogen digestibility [ 137 , 138 ]. Growing pigs fed diets containing dried mealworm at 10% had increased or similar energy and AA utilization as compared to pigs fed fish meal, meat meal, or PM [ 139 ].…”
Section: Protein-rich Feed Ingredientsmentioning
confidence: 99%